How Bad is Globalization for Labour Standards in the North? - Alejandro Donado; Klaus Wälde (FIW - Research Centre International Economics, 2010)
We analyse a world consisting of 'the North' and 'the South' where labour standards in the North are set by trade unions. Standards set by unions tend to increase output and welfare. There are no unions in the South and work standards are suboptimal. Trade between these two countries can imply a reduction in work standards in the North. Moreover, when trade unions are established in the South, the North, including northern unions, tends to lose out. Quantitatively, these effects are small and overcompensated for by gains in the South. The existing empirical literature tends to support our findings.
Keywords: J51; J81; F16; F21; 330; occupational health and safety; trade unions; international trade; welfare